A163 GIARDIA SP. METABOLOME : TOWARDS THE IDENTIFICATION OF NEW VIRULENCE FACTORS. (15th March 2019) - Allain, T; Groves, R; Lewis, I; Buret, A
Abstract: Background: Giardia duodenalis is a protozoan parasite responsible for giardiasis, a parasitic disease characterized by intestinal malabsorption, diarrhea, weight loss and abdominal pain. The pathophysiological processes occurring during giardiasis involve epithelial abnormalities, mucus depletion and microbiota disruption, however the mechanisms are poorly understood. Upon infection, Giardia, which has a minimal biosynthetic capacity, compete locally with the commensal microbiome for nutrients and ecological niches in the duodenum. Aims: In this context, we performed a metabolomic study to characterize the nutritional requirements and the secretome of several Giardia strains, isolated from human patients (assemblages A and B), outbreaks, as well as a variety of mammals. Methods: The metabolomic profiles of Giardia sp. isolates were determined using mass spectrometry. Trophozoites were grown to confluence in TYI-S-33 media and supernatants were collected at different time points (3, 6, 9, 12 and 24 hours) and mixed with ice cold methanol. Methanolic extracts were analyzed by Ultra High Performance Liquid Chromatography mass spectrometry and resolved by Hydrophilic interaction liquid chromatography column. Results: We identified a multitude of produced and consumed compounds such as amino acids, nucleic acid precursors, protein catabolism precursors, as well as carbohydrates and energy metabolites. Interestingly, nutrition requirements of Giardia trophozoites are significantly different between isolates, both intra and inter-assemblages. For instance, isolate WB6 (assemblage A) is more auxotrophic for arginine than GSM strain (assemblage B), while GSM strain requires more inosine, uridine and asparagine than other isolates. Conclusions: This study gives insight into how Giardia survives the host's intestinal tract and shows strain specific metabolomic signatures. A metabolomic approach may further help to understand the impact of nutritional modulation by Giardia trophozoites on the gut microbiome and host physiology. Funding Agencies: NRC